M HUBUNGAN KEKERASAN ANAK DENGAN MINAT DAN HASIL BELAJAR ANAK SEKOLAH DASAR - Megasari, Mona (JURNAL KESEHATAN KARTIKA, 2022)
Background: Violence against children is an intentional act that causes harm and endangers the child physically and emotionally. The impact of violence on children affects their physical, biological and social health, namely they are lazy about studying and children don't like lessons at school. Objective: This study was conducted to analyze the relationship between child violence and the interests and learning outcomes of elementary school children in Cireundeu. Method: This study is an analytical survey research with a cross-sectional desain. The sample for this study was 75 elementary school children in grades 4 and 5, where the tools used in this research were questionnaires and looking at transcripts of report cards for children's learning outcomes. Results: Based on the research results, it was found that there was a significant relationship between violence and children's interest in learning (p=0.003) and there was no significant relationship between violence and children's learning outcomes (p=0.961). Conclusion: Most children who frequently experience violence have low levels of interest and learning outcomes. The study can be a consideration for school teachers and parents to carry out preventive efforts, as well as increasing information for children, parents and teachers in improving the prevention of further violence by creating a conducive school environment and paying attention to students' relationships with their parents and school friends.